PWE-045 Management of anaemia in patients with inflammatory bowel disease: are we following the guidelines?. (22nd June 2015) - Ahmed, HME; Gadour, EMO E; O'Connor, A; Selinger, CP
Abstract : Introduction: Anaemia is a common finding in patients with Inflammatory Bowel Disease (IBD). The British Society of Gastroenterology (BSG) has published a comprehensive set of guidelines for approaching this problem in patients with IBD in 2010. The aim of this audit was to evaluate current practice in screening and managing anaemia in IBD patients compared to BSG guidelines standards. Method: IBD patients attending clinic and telephone clinics during a 2 week period in July and August 2014 at St. James's University Hospital, Leeds were assessed retrospectively. Data collection included any haematological tests performed during the preceding year, investigations and therapy for anaemia. Results: Monitoring for anaemia during the preceding year occurred in 119 of 122 (98%) eligible patients. 3 patients didn't have haemoglobin checked annually (one of them due to non-compliance). Of the included 119 patients 56% were female with a median age of 41 years (range 18–80). 49% had a diagnosis of Crohn's disease and 51% of ulcerative colitis. Anaemia was detected in 33 (24 females, 9 males, 17 Crohns disease, 16 ulcerative colitis) patients (28%). 6 females with anaemia were above the age of 50 and likely post menopausal. Anaemia was significantly more common in female patients (p = 0.038). 15 patients had microcytic hypochromic anaemia, but only 8 patients (53%) had appropriate Iron studies (Ferritin + CRP, followed by Iron + Transferrin saturation + TIBC if indicated) performed as per guidelines. Iron therapy was commenced orally in 4 cases and intravenously in 2 cases. 3 patients (37.5%) with confirmed Iron deficiency Anaemia (IDA) did not receive iron therapy. 5 patients had macrocytic anaemia. In 80% of these Vitamin B12 and folate were checked as per guidelines. Conclusion: Anaemia occurs in a third of IBD patients. While monitoring for anaemia was achieved in 98% overall compliance with guidelines was suboptimal. Especially investigations and treatment for iron deficiency anaemia requires further improvement. An emphasis on managing anaemia in IBD patients should be encouraged and appropriate educational measures implemented. Local guidelines for managing anaemia in IBD with a checklist style proforma to be added to patients' notes may improve adherence to recommendations. Disclosure of interest: None Declared. References: Guidelines for the management of inflammatory bowel disease in adults Mowat C, Cole A, Windsor A, et al . Gut. 2011